Zuid-Afrika - 11. Apartheid algemeen/politieke economie ZA
Dia-archief AABN: 11.1 Apartheid algemeen/regeringsbeleid; 11.2 Blanke bevolking/organisaties; 11.3 Politieke structuren; 11.4 Economie ZA. Met bijlage K88/782.